2001
DOI: 10.1074/jbc.m107871200
|View full text |Cite
|
Sign up to set email alerts
|

K+ Stimulates Specifically the Autokinase Activity of Purified and Reconstituted EnvZ of Escherichia coli

Abstract: The histidine kinase/response regulator system EnvZ/ OmpR of Escherichia coli regulates transcription of the genes ompF and ompC, encoding two porins of the outer membrane. Although the total amount of OmpF and OmpC remains constant, the relative levels of the two proteins fluctuate in a reciprocal manner depending on medium osmolality. The membrane-anchored sensor EnvZ somehow monitors changes in environmental osmolality. To characterize the nature of the stimulus perceived by EnvZ, this protein was overprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 49 publications
2
36
0
Order By: Relevance
“…They are most consistent with a model in which the autophosphorylation of EnvZ or the phosphotransfer to OmpR (or both) increases with increasing osmolarity. This view is further supported by a recent study that reported elevated EnvZ autokinase activity at high potassium concentrations, with no change in the phosphotransfer or phosphatase activities (30). Spontaneous dephosphorylation of OmpR-P would then lead to OmpR-P decay.…”
Section: Phosphorylation Decreases the Affinity Of Ompr Forsupporting
confidence: 68%
“…They are most consistent with a model in which the autophosphorylation of EnvZ or the phosphotransfer to OmpR (or both) increases with increasing osmolarity. This view is further supported by a recent study that reported elevated EnvZ autokinase activity at high potassium concentrations, with no change in the phosphotransfer or phosphatase activities (30). Spontaneous dephosphorylation of OmpR-P would then lead to OmpR-P decay.…”
Section: Phosphorylation Decreases the Affinity Of Ompr Forsupporting
confidence: 68%
“…Studies on these chimaeric proteins [13,14], combined with mutagenesis analysis [15,16], have shown that the transmembrane, as well as the linker helices, plays a role in signal propagation. While in vitro studies on reconstituted E. coli EnvZ have shown a response to changes in K + concentration [17], the mechanisms underlying the sensing function have not been elucidated. Replacement of up to 91 amino acids (Met 56 -Arg 146 ) from the C-terminal region of EnvZ per with the non-homologous periplasmic domain of PhoR had no effect on the regulation of OmpF and OmpC expression [18], thus putting in question the role of EnvZ per in sensing osmolarity signal(s).…”
Section: Introductionmentioning
confidence: 99%
“…the transporters ProP of E. coli (Culham et al, 2003), BetP of C. glutamicum (Rübenhagen et al, 2001) and OpuA of L. lactis (van der Heide et al, 2001), and the sensor kinases KdpD and EnvZ of E. coli (Jung et al, 2001). We observed that BetT mutants carrying C-terminal deletions of 6, 12 or 18 amino acid residues displayed a gradual loss in osmotic activation of choline transport.…”
Section: Discussionmentioning
confidence: 67%